Mechanical performance of roller compacted concrete pavement containing crumb rubber and nano silica - Mohammed, B.S. (Elsevier Ltd, 2018)
In this study, roller compacted rubbercrete (RCR) was developed by partially replacing fine aggregate with crumb rubber (CR) in roller compacted concrete pavement (RCCP) to improve its flexural resistance, ductile behavior and reduces the environmental effect of waste tires. Due to the fact that crumb rubber reduces strength in concrete, the addition of nano silica (NS) to mitigate the loss in strength of RCR is a possible solution. Sixteen mixtures with four levels of CR (0, 10, 20, and 30) by volume replacement to fine aggregate and four levels of NS (0, 1, 2 and 3) addition by weight of cementitious materials were prepared and tested. Fresh properties including density and Vebe consistency time have been determined. Hardened properties including unit weight, compressive, flexural and splitting tensile strength, elastic modulus, abrasion resistance and water absorption have been investigated. The findings show that CR increases the consistency of RCR. The compressive strength and abrasion resistance of RCR increases with 10 CR and the flexural strength also increases with replacement of up to 20 fine aggregate with CR. Addition of NS was successful in improving the performance of RCR due to its physicochemical effects which have been verified by carrying out microstructural analysis. Mathematical models developed using Response surface methodology for predicting the strengths and water absorption using CR and NS as the input variables shows a high degree of correlation and predictability. The results of multi-objective optimization showed that, an optimum mixture can be achieved with a 10 volume replacement of fine aggregate and 1.13 NS addition by weight of cementitious materials to have a high strength, durable and ductile RCR for pavement applications. Â© 2017 Elsevier Ltd